2019
DOI: 10.34019/1982-2243.2017.v21.27975
|View full text |Cite
|
Sign up to set email alerts
|

The intelligibility of English verbs in the simple past tense

Abstract: This study investigated the intelligibility of English verbs in the simple past inserted in sentences. The verbs were produced by two adult native speakers of English and six adult nonnative speakers, and they were transcribedby 13 adult Brazilian listeners. Results indicated that the intelligibility rate of regular verbs was similar to the irregular ones, and that the intelligibility of verbs produced by BP talkers was similar to the Spanish talkers. The intelligibility rate of German talkers, on the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, as occurred in Delatorre, Silveira and Gonçalves (2017) and displayed in Tables 3 and 4, the number of verbs with low intelligibility rate (lower than 21.4%) was higher than the number of verbs with high intelligibility (higher than 71%) in both intelligibility tests. For instance, the low intelligibility rates of verbs 'trained,' (ANTOSEN, 2007), which may be used in English as an L2 (YAVAS, 1994).…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…On the other hand, as occurred in Delatorre, Silveira and Gonçalves (2017) and displayed in Tables 3 and 4, the number of verbs with low intelligibility rate (lower than 21.4%) was higher than the number of verbs with high intelligibility (higher than 71%) in both intelligibility tests. For instance, the low intelligibility rates of verbs 'trained,' (ANTOSEN, 2007), which may be used in English as an L2 (YAVAS, 1994).…”
Section: Resultsmentioning
confidence: 60%
“…However, Munro and Derwing (2015) propose that studies on L2 pronunciation may go further and focus on L2 learners' intelligibility (i.e., how much an utterance is actually understood), for instance. Silveira et al (2017) revealed that most studies conducted in Brazil have focused on the perception and production of single segments in cross-sectional studies, and few of them had investigated suprasegmental features or the intelligibility of English sounds.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations